IMPROVING COMMUNITY FINANCIAL GOVERNANCE: THE CASE OF POKDARWIS KAMPUNG KERANGGAN, SOUTH TANGERANG CITY - Setiono, Bambang; Handayani, Sri; Bahri, Asep Syiaful; Dewobroto, Wisnu Sakti (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
We introduced a financial governance module and digital accounting system to Kelompok Sadar Wisata (Pokdarwis) in Kampung Keranggan, Tangerang City, Banten Province. Pokdarwis Kampung Keranggan is renowned for its community-driven initiative to transform an underutilized area on the outskirts of Tangerang into a vibrant Edu-tourism destination. This community outreach program has provided significant opportunities for Pokdarwis to improve the community’s financial governance. Zahir Online address challenges such as limited human and financial capital, offering an accessible platform for better financial management. However, the success of this initiative relies heavily on community participation and education. While technology can compensate for a lack of accounting skills and experience, it cannot resolve low levels of engagement or reluctance to adopt new systems, as evidenced by Pokdarwis’ preference for Excel over Zahir Online. Without active participation from the community, Pokdarwis risks undermining its effectiveness and the outcomes of this community outreach program. The community's role is integral, given that Pokdarwis functions as a representative and steward of communal resources.